Carbon sequestration under asana (Bridelia retusa) based agroforestry systems in red ferruginous Alfisols - Meshram, N.A. (Indian Journal of Agroforestry, 2025)
An experimental study was conducted at the Research Farm of AICRP on Agroforestry, Dr. BSKKV, Dapoli, Maharashtra during 2019 and 2020. The experiment was laid out in a randomized block design (RBD) with eight treatment and three replications. The results emerged out indicated that significantly high carbon sequestration, growth performance of Asana based agroforestry were recorded by T6>T4>T5 than other. The carbon sequestration was found highest in T6 this may due to high availability of plant biomass addition in soil. The above ground biomass (AGB) (153.58 t ha-1) and (166.25 t ha-1) and below ground biomass (BGB) (38.40 t ha-1) and (40.90 t ha-1) were highly recorded by T6 in the year of 2019 and 2020. However, plant leaves C % (38.03%) and (39.00%), woody branches C % (42.47 %) and (42.97 %), branches C % (38.02 %) and (39.04 %) were highly recorded by T6 in the year of 2019 and 2020. Similarly, carbon (%) (8.12 % ) and (8.42 %), plant carbon stock ( 75.83 t ha-1) and (83.83 t ha-1), soil carbon stock ( 33.20 t ha-1) and (34.76 t ha-1), plant carbon sequestration (95.99 t ha-1) and (103.91 t ha-1) as well as soil carbon sequestration (3.197 t ha-1) and total carbon sequestration rate (7.32 t ha-1) were highly recorded by T6 in both the year. The study showed that the T6-Asana + Jam agroforestry system sequestered more carbon than other treatments; it may be due to presence of high amount biomass and addition organic matter of that system. Overall, it can be concluded that the higher growth performance, more carbon sequestration were recorded significantly by (T6) Asana + Jam (Syzygium samarangense) followed by Asana + Morus alba (T4) than other. Thus, Asana + Jam agroforestry system was sequestered more carbon in lateritic soils of Konkan.